2015
DOI: 10.18632/oncotarget.3028
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cellular prion protein (PrPc) under hypoxia inhibits apoptosis caused by TRAIL treatment

Abstract: Hypoxia decreases cytotoxic responses to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) protein. Cellular prion protein (PrPc) is regulated by HIF-1α in neurons. We hypothesized that PrPc is involved in hypoxia-mediated resistance to TRAIL-induced apoptosis. We found that hypoxia induced PrPc protein and inhibited TRAIL-induced apoptosis. Thus silencing of PrPc increased TRAIL-induced apoptosis under hypoxia. Overexpression of PrPc protein using an adenoviral vector inhibited TRAIL-induced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Therapeutically, we provide experimental evidence that combinatorial treatment strategies with TRAIL and SMAC mimetics or XIAP-targeting drugs overcome the apoptosis-hampering conditions imposed by the hypoxic tumor microenvironment. Our findings extend previous approaches to overcome hypoxia-induced apoptosis resistance [29, 30] and also have a broad clinical applicability in colorectal cancer cells exhibiting TRAIL-resistance under normoxia.…”
Section: Discussionsupporting
confidence: 84%
“…Therapeutically, we provide experimental evidence that combinatorial treatment strategies with TRAIL and SMAC mimetics or XIAP-targeting drugs overcome the apoptosis-hampering conditions imposed by the hypoxic tumor microenvironment. Our findings extend previous approaches to overcome hypoxia-induced apoptosis resistance [29, 30] and also have a broad clinical applicability in colorectal cancer cells exhibiting TRAIL-resistance under normoxia.…”
Section: Discussionsupporting
confidence: 84%
“…Although the discovery of factors that cause CRC give new insights into the growth and metastasis of CRC, there is still little information on the etiology of most CRC, therapeutic agents, and anti-CRC targeting molecules. However, cellular prion protein (PrP c ) expression has been identified as a risk or susceptibility factor for developing CRC (17). In essence, PrP c is a highly conserved cell-surface glycoprotein that has been identified in all vertebrates, with the same protein sequence as the prion proteins that cause scrapies in sheep, bovine spongiform encephalopathy in cattle, and kuru in human beings (18,19).…”
Section: Furthermore We Provide Evidence For the Therapeutic Applicamentioning
confidence: 99%
“…As previously mentioned, PrP C also is regulated by HIF, and PrP C expression is increased under hypoxic conditions. Park et al ( 3 ) demonstrated that the effects of HIF-1α and PrP C on neuronal cell death are prion peptide-induced. In hypoxic conditions, neurons are protected from PrP-induced cell death via the activation of p65 and HIF-1α and subsequent inactivation of p21 and p53 signals.…”
Section: Hif-1α Regulates Prp Cmentioning
confidence: 99%
“…For these reasons, recent research has focused on obtaining more conclusive information about the functional role of PrP C in tissue regeneration. Additionally, regulating PrP C expression by hypoxia has become an important topic ( 3 ). Hypoxia occurs when blood oxygen concentrations are insufficient and long periods of hypoxia can induce cell death.…”
Section: Introductionmentioning
confidence: 99%